Burnout Among ICU and Non-ICU Healthcare Professionals in Saudi Arabia: A Comparative Cross-Sectional Analysis - Krishna GG; Harbli NMA; Krishnan N; Ghundul LB; Aldhahri R; Aldossary AB; Margalani AO; Almeshari M; Alwadeai KS; Alshehri RA; Alkhathami AAA; Sreedharan JK; et al. (Journal of Multidisciplinary Healthcare)
Gokul G Krishna,1 Noran Mohammed Ali Harbli,1 Nanditha Krishnan,1 Lamees Bandar Ghundul,1 Rana Aldhahri,1 Amna Badar Aldossary,1 Aaya Osama Margalani,1 Mohammed Almeshari,2 Khalid S Alwadeai,2 Riyadh A Alshehri,3 Abdulrahman Ali A Alkhathami,4 Jithin K Sreedharan,5 Ayedh Dhafer AlAhmari2 1Department of Respiratory Therapy, Batterjee Medical College, Jeddah, Saudi Arabia; 2Department of Rehabilitation Health Sciences, College of Applied Medical Sciences, King Saud University, Riyadh, Saudi Arabia; 3Department of Respiratory Care Services, King Abdullah Specialized Children Hospital, Jeddah, Saudi Arabia; 4Department of Specialized Therapy and Clinical Services, John Hopkins Aramco Healthcare, Dhahran, Saudi Arabia; 5Department of Respiratory Therapy, College of Health Sciences, University of Doha for Science and Technology, Doha, QatarCorrespondence: Ayedh Dhafer AlAhmari, Department of Rehabilitation Health Sciences, College of Applied Medical Sciences, King Saud University, Riyadh, Saudi Arabia, Tel +966 503477448, Email aalahmari9@ksu.edu.saPurpose: Burnout syndrome is a significant concern among healthcare workers, particularly in the high-stress environment of ICUs. This study evaluates and compares the levels of burnout among healthcare workers in the ICU and non-ICU settings and to assess the influence of sociodemographic characteristics.Materials and Methods: A cross-sectional survey was conducted using MBI questionnaire, which measures emotional exhaustion (EE), depersonalization (DP), and personal accomplishment (PA).Results: Among 844 participants (51.7% female), most were aged 25– 34 (41.9%), single (46.7%), and worked in non-ICU settings (61.8%). They predominantly worked in governmental hospitals, with 1– 4 years of experience (46.8%), managing 6– 10 patients per shift (36.5%), and working 16– 20 shifts monthly (75.8%). ICU staff reported significantly higher EE (21 [18] vs 11.5 [15], p ≤ 0.0001) and DP (17 [19] vs 8 [12], p ≤ 0.0001), and lower PA (35 [19] vs 42.5 [12], p ≤ 0.0001). Post-hoc analysis showed ICU workers were significantly more prone to moderate (Adj. Resid. = 3.57, p< 0.001) and severe EE (Adj. Resid. = 5.20, p < 0.001). In the DP domain, they were more likely to experience severe DP (Adj. Resid. = 9.22, p< 0.001). Severe burnout in PA was also more likely among ICU staff (Adj. Resid. =5.67, p< 0.001). Nurses and RTs reported higher EE and DP. Married ICU staff had lower EE (OR: 0.453) but higher DP (OR: 1.623). Factors like 6– 8 years of experience, 8-hour shifts, and fewer monthly shifts were associated with reduced EE and higher PA, while additional jobs were linked to increased DP.Conclusion: ICU healthcare workers experienced significant burnout compared to non-ICUs staff, with nurses and RTs being the most affected. Sociodemographic factors such as marital status, years of experience, shift duration, and holding additional jobs increased burnout risk. These findings underscore the need for targeted interventions in high-stress environments like the ICU.Keywords: long term stress, healthcare employees, emotional exhaustion, depersonalization, personal accomplishment, occupational stress